Economic integration and the margins of exports in Nigeria: Implications for AfCFTA - Damilola Felix Arawomo; Adegoke Ibrahim Adeleke (West African Journal of Monetary and Economic Integration, 2022)
This paper explores the effects of economic integration on intensive and extensive export margins of Nigeria's trade with ECOWAS and other African countries. Multiple indices of economic integration and the margins of exports are computed. Fractional Logit model is used to estimate the intensive export margin equations while the Two-Stage Least Square (2SLS) is adopted for the estimation of the extensive export margin equations. Based on Regional Orientation Index, Nigeria recorded improved economic integration with ECOWAS and African countries in chemicals, beverages and tobacco, and manufactured products. However, Nigeria's margins of exports are still generally low with the Africa region and ECOWAS sub-region. Economic integration is found to have significant effects on extensive export margin but an insignificant effect on intensive export margin. Foreign and domestic investments are found to be the major drivers of export margins, and these could be achieved through improved ease of doing business. In preparation for the implementation of AfCFTA, it becomes imperative for Nigeria to intensify efforts in the production of manufactured, chemical, beverages, and tobacco products in which Nigeria has improved economic integration. Concerted efforts are thus required for Nigeria to be more competitive in both ECOWAS and AfCFTA.
Keywords: F14; F15; R10; R11; 330; Economic Integration; Extensive; Intensive; Export Margins